Structure characterization of soybean peptides and their protective activity against intestinal inflammation. (1st September 2022) - Wen, Lingrong; Bi, Huimin; Zhou, Xuesong; Jiang, Yueming; Zhu, Hong; Fu, Xiong; Yang, Bao
Highlights: Fifty-two soybean peptides were identified by UHPLC-MS/MS. The anti-inflammatory mechanism was revealed. Soybean peptides beneficial to gut health were produced. Abstract: Soybean peptides serve as functional foods with impressive health benefits. The structure characteristics of peptides are highly related to the health benefits. The structure–activity relationship and mechanism underlined are important scientific questions in this field. To answer these questions, soybean peptides were produced by combinatory enzymatic hydrolysis in this work. Fifty-two peptide sequences were identified by ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). The anti-inflammatory activities of these peptides were investigated by using a lipopolysaccharide (LPS)-induced inflammation cell model. Soybean peptides could significantly promote cell proliferation. Additionally, soybean peptides could alleviate LPS-induced inflammation by reducing the production and expression of nitric oxide (NO), tumor necrosis factor alpha (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6). Moreover, soybean peptides could promote the mRNA expression of proteins related to inflammation inhibition (IL-10) and tight junction modulation. The structure–activity relationship was addressed. The results documented the potential of soybean peptides as functional foods.